UNDERSTANDING EDUCATORS’ EXPERIENCE AND ATTITUDE TO GAMIFIED LEARNING APPLICATIONS - Anastasiia V. Tokarieva; Inna V. Сhyzhykova (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
This article is devoted to the analysis of the experiences and attitudes of Ukrainian educators to gamified learning applications (GLAs) in the context of a new educational paradigm formation. With the metaskills (collective intelligence, a variety of thinking styles, empathy, etc.) coming to the foreground, the development of innovative technologies and teaching approaches that would enhance students’ cognitive, motivational and social potential, skills of team-working, problem-solving, and critical thinking are becoming important. As the result, the necessity of educational paradigm’s change and of designing new learning models that will be relevant for students of the XXI century are obvious. To meet this challenge, digital pedagogy, playful learning, gamification and educational digital games are gradually getting their part in everyday toolkit of educators. The present article attempts to analyse how educators from Ukraine interact with and relate to gamified learning applications. Gamified learning applications (GLAs) in this research are defined as a wide spectrum of digital tools that includes educational games (for example, “Pandemic”, game “Fake News”, “Backpack”, “Trivia Time”); interactive quizzes (for example, “Kahoot”, “Quizlet”, “ClassDojo”, “Edmodo”); virtual game universes (for example, “Minecraft Edu”, “Second Life”, “Hytale”); gamified learning management systems (for example, “Classcraft”, “Lingua Attack”, “Socrative”, “DyKnow”). The principal tasks of the authors’ investigation in this work are: 1) the experience of educators from Ukraine in using gamified learning applications: frequency, titles and the main purposes of GLAs’ application; 2) the attitude of the educators to GLAs: skills that gamified learning applications can develop in students, the educators’ outlook on gamified learning applications; 3) educational potential of GLAs as seen by the educators: advantages of GLAs, possible difficulties that prevent teachers from using gamified learning applications as an educational tool. To solve the present tasks, a qualitative research method was used based on the questionnaire compiled and conducted within the frame of “Digital Technologies’ Application in the Process of Students’ Professional Skills’ Development in Ukrainian Universities” research project implementation (Department of Innovative Technologies in Pedagogy, Psychology and Social Work, Alfred Nobel University). The sample of the participants included 74 respondents. The research took place in December 2021 – January 2022. The results obtained can be summarised as follows: 1) gamified learning applications (GLAs) are becoming a part of an instructional toolkit of the Ukrainian educationalists; 2) the most popular GLAs used by educators from Ukraine are interactive quizzes, educational games and gamified learning systems; 3) the majority of the respondents see educational role as the main purpose of GLAs. The ability of GLAs to motivate, entertain and to create “communities of learning” are on the second place according to our data; 4) more than a half of the interviewed educators expressed their willingness to use gamified learning applications in their practice. At the same time, 16,7% are satisfied with the traditional methods and 4,2% feel it risky to use new teaching methods; 5) among the main obstacles to wider application of GLAs in practice are the absence of knowledge about GLAs, the low level of digital skills and technical challenges. The authors conclude that Digital Pedagogy formation as a new strong branch of Educational Sciences is on the stage of its formation globally, as well as in Ukraine. The need to develop serious video games’ and digital learning applications’ courses for educators with an integrated teacher-training program to help educators understand, design, evaluate and apply serious video games and GLAs into their practice, a Digital Learning Unit creation as an indispensable part of a contemporary Ukrainian Higher Educational Institution are seen as the vectors of further research and work.